Spin splitting of image-potential states on fcc Fe/Cu(100) - Thomann, Ulrich; Shumay, Igor; Weinelt, Martin; Fauster, Thomas (Applied Physics B-Lasers and Optics, 1999)
The ferromagnetic exchange splitting of the lowest image-potential states has been measured for Fe films on Cu(100). The majority and minority spin contributions were separated using polarization-dependent two-photon photoemission without magnetizing the sample. The results show an increased spin splitting for decreasing film thickness in agreement with the increasing magnetic moment found by band structure calculations. The lifetime of the states is between 3 fs and 15 fs with slightly shorter values for the minority state.